Grasping the Democratic Peace : Principles for a Post-Cold War World. - Russett, Bruce (Princeton University Press, 2001)
By illuminating the conflict-resolving mechanisms inherent in the relationships between democracies, Bruce Russett explains one of the most promising developments of the modern international system: the striking fact that the democracies that it comprises have almost never fought each other.